FIKIH MUAMALAH REVIEW OF AIRDROP BUSINESS ACTIVITIES USING DIGITAL ASSETS CRYPTOCURRENCY - Ibnu Mutakhir; Dedi Sunardi (Al-Muamalat: Jurnal Ekonomi Syariah, 2024)
This research is provided to examine cryptocurrency airdrop business activities as Hibah contracts in Fiqh muamalah, focusing on the Sharia framework and legal provisions in Indonesia. The main goal is to promote the promotion of new cryptocurrencies and increase the liquidity and value of cryptocurrencies. The research method used is the juridical normative research method, which specifically explores the implementation of norms, rules, and regulations contained in positive law and Islamic law. The research results confirm that the cryptocurrency airdrop business activities according to Fiqh Muamalah require fulfillment of the terms and conditions of the grant agreement, Ijarah agreement, and compliance with national legal provisions. In implementing an airdrop, crucial aspects such as the type of cryptocurrency being distributed, strict terms and conditions, and airdrop security are the main focus. Considering all these elements, it is hoped that cryptocurrency airdrop business activities can run efficiently and provide optimal benefits for all parties involved.